"Green-Colored Uyghur Poet": Religion, Nostalgia, and Identity in Contemporary Uyghur Poetry. (July 2022) - Zelcer-Lavid, Michal
There is wide consensus that Islam is an important rallying point for the Uyghurs and an essential component of their national identity. Yet despite its centrality in Uyghur culture, there is only marginal reference to religion in modern Uyghur poetry. In this article, I argue that poets such as Adil Tuniyaz, Tahir Hamut Izgil, and others, most of whom are secular and urban, choose to relate to religion through mysticism and nostalgia in reaction to the Chinese state's characterization of Islam as identified with violent fundamentalism and terrorism. By avoiding the use of separatist symbols, these poets contribute to a broad national ethos that strengthens contemporary Uyghur identity.